Breast cancer detection by dedicated breast positron emission tomography according to the World Health Organization classification of breast tumors. Issue 7 (July 2021) - Sasada, Shinsuke; Kimura, Yuri; Masumoto, Norio; Emi, Akiko; Kadoya, Takayuki; Arihiro, Koji; Okada, Morihito
Abstract: Objective: Considering the difficulty in detecting primary breast cancers using whole-body positron emission tomography (WBPET) owing to its limited spatial resolution, we aimed to evaluate the detectability of breast cancer by ring-type dedicated breast PET (DbPET) on the World Health Organization (WHO) histological classification in comparison with WBPET. Methods: A total of 938 patients with breast cancer underwent WBPET and ring-type DbPET, and 1021 lesions were histologically assessed based on the WHO classification of tumors of the breast. The findings of WBPET and DbPET were retrospectively evaluated and compared. Results: The size-related sensitivity of DbPET was superior to that of WBPET for subcentimetric tumors (81.9% vs. 52.4%, P  < 0.001). The histological distribution was as follows: 11 lobular carcinoma in situ, 158 ductal carcinoma in situ, 738 infiltrating duct carcinoma not otherwise specified (NOS), 12 lobular carcinoma NOS, 40 mucinous adenocarcinoma, 13 tubular carcinoma, 36 invasive breast carcinoma others, and 13 papillary neoplasms. WBPET had low sensitivity for lobular carcinoma in situ, ductal carcinoma in situ, lobular carcinoma NOS, mucinous adenocarcinoma, and tubular carcinoma. DbPET showed improved sensitivity for all the above except lobular and tubular carcinoma. The maximum standardized uptake values (SUVmax) of DbPET were significantly higher than those of WBPET for histological types, excluding lobular carcinoma in situ. The SUVmax of papillary neoplasms was high regardless of low-grade histology and Ki-67 labeling index. Conclusions: DBPET was found to have high sensitivity and SUVmax values for all histologic types that showed low sensitivity of detection on WBPET, except lobular carcinoma in situ. Highlights: Detection of primary breast cancer by dedicated breast PET was evaluated based on the WHO classification. Dedicated breast PET showed high sensitivity and SUVmax values for all breast cancer histologic types that showed a low sensitivity of detection on whole-body PET, except lobular carcinoma in situ. Dedicated breast PET findings represent histology-specific features.